Trends in vacancy distribution and hardness of high temperature neutron irradiated single crystal tungsten. (1st October 2020) - Bonny, G.; Konstantinovic, M.J.; Bakaeva, A.; Yin, C.; Castin, N.; Mergia, K.; Chatzikos, V.; Dellis, S.; Khvan, T.; Bakaev, A.; Dubinko, A.; Terentyev, D.
Abstract: The aim of the present study is to extend the knowledge about the formation and thermal stability of vacancy-type defects in tungsten under neutron irradiation, thereby mimicking the temperature and neutron flux expected in the ITER divertor. Neutron irradiation of single crystal tungsten, W(100), in the temperature range 600-1200 °C is performed up to 0.12 dpa. Positron annihilation spectroscopy is employed to detect the presence of open volume defects, while hardness tests are applied to relate the irradiation-induced defects with the modification of mechanical properties. Rationalization of the experimental results is enhanced by the application of a kinetic Monte Carlo simulation tool, applied to model the microstructural evolution under the neutron irradiation process. The relation between radiation microstructure and hardness is explained via a dispersed barrier model. Graphical abstract: Image, graphical abstract